2018
DOI: 10.1007/s11060-018-03015-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptoms in glioma patients throughout the disease trajectory: a systematic review

Abstract: BackgroundGlioma patients suffer from a wide range of symptoms which influence quality of life negatively. The aim of this review is to give an overview of symptoms most prevalent in glioma patients throughout the total disease trajectory, to be used as a basis for the development of a specific glioma Patient Reported Outcome Measure (PROM) for early assessment and monitoring of symptoms in glioma patients.MethodsA systematic review focused on symptom prevalence in glioma patients in different phases of diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(77 citation statements)
references
References 62 publications
(86 reference statements)
4
73
0
Order By: Relevance
“…These pathological waves involve massive intracellular calcium influx mediated in part by NMDA receptor activation that transiently silences neuronal activity and briefly impairs the precise coding of high-frequency synaptic inputs in recovering neurons (55). SD appearance in brain tumors is of clinical relevance and may contribute to common transient neurological symptoms including confusional spells, motor deficits, and headache in glioma patients (56).…”
Section: Discussionmentioning
confidence: 99%
“…These pathological waves involve massive intracellular calcium influx mediated in part by NMDA receptor activation that transiently silences neuronal activity and briefly impairs the precise coding of high-frequency synaptic inputs in recovering neurons (55). SD appearance in brain tumors is of clinical relevance and may contribute to common transient neurological symptoms including confusional spells, motor deficits, and headache in glioma patients (56).…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 32 studies, 25 common symptoms were identified in glioblastoma patients, with the following being most prevalent: seizures (37%), cognitive deficits (36%), drowsiness (35%), dysphagia (30%), headache (27%), confusion (27%), aphasia (24%), motor deficits (21%), fatigue (20%) and dyspnea (20%). [ 15 ] There is variability within the disease trajectory, with more headache and dizziness at the time of diagnosis, higher rates of treatment side effects during the follow-up phase, and more drowsiness, fatigue, and neurologic deficits in the end-of-life phase. Symptom burden increases during active HGG treatment and hospitalizations, and there is a phase of significant and progressive worsening at the end of life.…”
Section: Approachmentioning
confidence: 99%
“…The term glioma is a general name of different types of gliomas, such as glioblastoma (high‐grade tumour), oligodendroglioma or astrocytoma. According to a recent review study, there are 25 symptoms (such as anorexia, cognitive deficits, alopecia and anxiety/depression) in glioma patients in different phases [3]. The five most common symptoms are headache (27%), dysphagia (30%), drowsiness (35%), cognitive deficits (36%) and seizures (37%) [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent review study, there are 25 symptoms (such as anorexia, cognitive deficits, alopecia and anxiety/depression) in glioma patients in different phases [3]. The five most common symptoms are headache (27%), dysphagia (30%), drowsiness (35%), cognitive deficits (36%) and seizures (37%) [3]. The most prevalent type of glioma is glioblastoma that can evolve rapidly over several weeks.…”
Section: Introductionmentioning
confidence: 99%